Pain and Depression Are Associated With More Anxiety in ME/CFS: A Cross-Sectional Cohort Study Between Norway and Spain. (October 2020) - Strand, Elin Bolle; Castro-Marrero, Jesús; Helland, Ingrid; Alegre, Jose; Mengshoel, Anne Marit
Objectives: Lasting, unexplained and high levels of pain may cause anxiety in patients with chronic fatigue syndrome. The objectives of the current study were to test assumptions of the association between pain and anxiety in patients diagnosed with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) and to clarify the role of depression in this relationship. Methods: Data were collected from 664 participants (age 18-65 years) with 133 ME/CFS patients and 201 healthy controls from Norway and 330 CFS patients from Spain. Binary logistic regression model was applied to test relationships between the included variables in the samples. Results: Both pain and depression made significant direct contributions to the level of anxiety. The strongest risk for higher levels of anxiety was the combination of high levels of depression and high levels of pain in the overall sample (OR = 49.70; P  < 0.001), not so much in the Spanish cohort (OR = 11.99; P  < 0.0001) and most of all in the Norwegian cohort (OR = 88.21; P  < 0.001) sample. Conclusions: It was the combination of high pain levels and high levels of depression that to the greatest extent increased the risk of anxiety in patients with CFS/ME. Whatever diagnostic criterion that is applied, anxiety and depression should be mandatory to assess in the clinical assessments performed for diagnosing the ME/CFS. Approaches addressing anxiety-related pain and treatment of depression should be warranted.